Relationship between the fatty acid profile of hair and energy availability of lactating primiparous cows. Issue 1 (18th December 2018) - Möller, Ramona; Dannenberger, Dirk; Nürnberg, Gerd; Strucken, Eva-Maria; Brockmann, Gudrun A.
Abstract: We hypothesised that a relationship would exist between hair fatty acids, especially C12:0, C14:0 and C16:0, and parameters of energy metabolism such as energy intake, energy mobilisation, and energy requirement for maintenance and milk performance. For this study, 11 primiparous German Holstein cows were available from which hair samples at weeks 6 and 8 of lactation were analysed. The average body weight of these animals was 558 ± 27 kg at calving and milk yield at 100-days in milk was 3, 537 ± 529 kg. Feed intake and milk yield were measured daily. Body weight and back fat thickness were measured at calving and in weeks 2, 4, and 8 of lactation. Energy balance and energy utilisation were calculated until week 6 of lactation. Spearman's correlation coefficients were found to be significantly positive for the relationship between the percentage of C12:0 and C14:0 fatty acids in the hair in lactation week 8 and energy intake in weeks 5 and 6 (0.62 < r < 0.65, P < 0.05). If the animals are grouped according to their energy utilisation between weeks 1 and 6 into two groups higher ( n = 6) or lower ( n = 5) than the median, animals of the high energy utilising group had a higher energy intake. These animals had also higher percentages of the C12:0 fatty acid in their hair fat (week 6: 4.9% vs . 3.1%, P < 0.05; week 8: 4.3% vs. 2.9%, P = 0.05). Our hypothesis is supported, and this study justifies further investigation of the content of medium-chain fatty acids in hair samples as biomarkers for the metabolic status of a cow during early lactation.